2008
DOI: 10.1007/s10354-008-0515-1
|View full text |Cite
|
Sign up to set email alerts
|

Early Austrian multicenter experience with palonosetron as antiemetic treatment for patients undergoing highly or moderately emetogenic chemotherapy

Abstract: Palonosetron resulted in high antiemetic efficacy in this study. Female gender and age < or = 50 years should be particularly considered when the antiemetic regimen is selected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, Tang et al [19] reported that 30 µg/kg of palonosetron is the effective dose in reducing postoperative vomiting. In addition, a post-marketing surveillance reported tolerable adverse events at a higher dose of palonosetron in prophylaxis for CINV [20]. Therefore, we think that studies are necessary to determine the efficacy and safety of higher doses of palonosetron in the prevention of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…However, Tang et al [19] reported that 30 µg/kg of palonosetron is the effective dose in reducing postoperative vomiting. In addition, a post-marketing surveillance reported tolerable adverse events at a higher dose of palonosetron in prophylaxis for CINV [20]. Therefore, we think that studies are necessary to determine the efficacy and safety of higher doses of palonosetron in the prevention of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…However, palonosetron is known to be safe at even higher doses [14,15]. Furthermore, Y-site administration of palonosetron has been reported to be compatible and stable with fentanyl [16].…”
Section: Discussionmentioning
confidence: 99%
“…Since palonosetron was approved by FDA, several more phase II and phase III trials have been published which may help clarify the above issues. 44,58–64 These are summarized in Table 2.…”
Section: Chemistry Mechanism Of Action and Pharmacokinetic Profilementioning
confidence: 99%